Peningkatan Peran Suami Kepada Anak Pertama Mengenai ASI Eksklusif di Kota Bengkulu - Uun Yuniarti; Bintang Agustina Pratiwi; Ivan Acmad Nurcholis; Emi Kosvianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Exclusive breastfeeding during the first six months of a baby's life is an important foundation for optimal growth and development. However, the success of an exclusive breastfeeding program is not only determined by the role of the mother, but also depends heavily on the support of the husband as the main companion. This community service activity aims to increase the involvement of husbands in supporting exclusive breastfeeding for the first child through an educational and participatory approach. The target of this activity was a married couple who were waiting for the birth of their first child in Bengkulu City. The implementation of the program is carried out through a series of activities in the form of counseling, interactive discussions, and continuous assistance during pregnancy up to six months after childbirth. Evaluation was carried out using pretest and posttest to measure changes in knowledge and attitudes, as well as observation of the husband's direct involvement in the breastfeeding process. The results showed a significant increase in husbands' knowledge and attitudes towards the importance of exclusive breastfeeding, as well as an increase in their involvement in supporting their wives both emotionally and practically. These findings confirm that education that actively involves husbands can be an effective strategy in supporting the success of exclusive breastfeeding. Therefore, breastfeeding counseling and mentoring programs in the community should be designed holistically by involving both parents as a supportive unit.